Locked Anterior-Inferior Sternoclavicular Joint Dislocation: A Case Report. Issue 2 (April 2021) - Ben-Ari, Erel; Magone, Kevin M.; Lowe, Dylan T.; Costas, Bizekis; Rokito, Andrew S.; Virk, Mandeep S.
Update: This article was updated onMay 26, 2021 because of a previous error. One of the author's name was incorrect. The correct name is Costas Bizekis An erratum (JBJS Case Connect. 2021;11[2]:e20.00780ER) has been published for this article. Case: We report a rare variant of sternoclavicular joint (SCJ) dislocation, namely locked anterior-inferior dislocation, with unique clinical, radiographic, and intraoperative findings. In this variant, the medial clavicle was displaced anteriorly and inferiorly and locked in the manubrial-intercostal space, with corresponding mechanical dysfunction of the ipsilateral shoulder girdle joints. Symptoms unique to this variant included painful neck spasms and limited glenohumeral elevation. Nonsurgical treatment was not successful, and open reduction and ligament reconstruction resulted in correction of the fixed deformity with resolution of the clinical symptoms. Conclusion: Locked anterior-inferior SCJ dislocation is indicated for early open reduction and ligament reconstruction.